MANAGING PUBLIC SERVICES making informed choices. - Lapsley, Irvine; Mattisson, Ola (ROUTLEDGE, 2021)
This book explores innovations in public management, including establishing a corporate vision, strategizing an organization and change management. Chapters provide a valuable frame of reference for the 21st-century manager of public services by assessing the renewal of existing practices such as strategic costing, performance management, digitization and procurement and innovations in management practices, including branding, Lean Management, resilience and risk management. The book suggests that, as the management of public services is imbued with financial, social, economic and political uncertainties, management needs to be flexible and responsive to new ideas and practices to fulfil its purpose. This book ultimately supports the reflective manager, those who think about their job and are open to new ideas on how their job can be done better, by revisiting existing practices and examining innovations in public management. Enriched with real-life cases and thought-provoking discussion questions, this is the ideal textbook for reflective, open-minded advanced students of public management and actual, or aspiring, reflective managers in public services.